OCULAR BLOOD FLOW IN PROLIFERATIVE DIABETIC RETINOPATHY PATIENT’S VS NON-PROLIFERATIVE DIABETIC RETINOPATHY- A COMPARISON STUDY. - Dr. Karen Josephine Rayen; Dr. Sheela M; Dr. Prof. K Kanmani; Dr. Ajay A; Dr. Atchaya Sivanandam (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND: Diabetic retinopathy (DR) is a leading cause of vision impairment worldwide, characterized by changes in ocular blood flow that, progress from non-proliferative diabetic retinopathy (NPDR) to proliferative diabetic retinopathy (PDR). In the field of ophthalmology, these hemodynamic changes are crucial for early diagnosis and therapeutic interventions. In this background, the present study aims to compare ocular blood flow parameters in patients with PDR and NPDR to identify significant differences that may contribute to disease progression.METHODOLOGY: In the present study, we received ethical and scientific approval before commencing data collection. Patients visiting ophthalmology outpatient services were screened, and those meeting the inclusion criteria provided informed consent. This prospective study included three groups;10 patients with proliferative diabetic retinopathy (PDR), 10 with non-proliferative diabetic retinopathy (NPDR), and 10 healthy controls. Ocular blood flow velocities in the ophthalmic artery, short posterior ciliary artery, central retinal vessels, and vortex veins were measured, including systolic, end-diastolic, and mean arterial velocities. Each assessment was completed in a single session of 45–60 minutes, confirming strict confidentiality. This data was analyzed using the Statistical Package for Social Studies (SPSS). RESULTS: In the study of ocular blood flow in diabetic retinopathy, participants with PDR had an average age of 53.27 ± 10.35 years, while those with NPDR averaged 55.18 ± 12.47 years. In the study of maximum diastolic blood flow velocity, patients with PDR exhibited significantly lower velocities compared to those with NPDR in several vessels.CONCLUSION: Retinal blood flow is significantly altered in diabetic retinopathy, with PDR patients exhibiting reduced velocities in key ocular vessels compared to NPDR, representing impaired circulation. These findings highlighted the role of hemodynamic changes in the progression of diabetic retinopathy and suggest that assessing ocular blood flow may aid in early detection and targeted interventions to prevent vision loss in diabetic patients.